Diffuse Large B-cell lymphoma: Prognostic markers and their impact on therapy. Issue 5 (3rd May 2016) - Jamil, Muhammad O.; Mehta, Amitkumar
ABSTRACT: Diffuse large B-cell lymphoma (DLBCL) is the most common type of Non-Hodgkin lymphoma (NHL). DLBCL is clinically, pathologically and molecularly heterogeneous disease. Various clinical, pathological and molecular markers have been developed to characterize the disease. Based on these characterizations, new targeted agents are being investigated to optimize the treatment and improve the outcomes of DLBCL. Enhanced molecular understanding, invention of targeted agents and immunotherapy has opened the doors for improvement in the treatment of DLBCL. In this review, we will discuss various prognostic markers of DLBCL and their potential therapeutic implications.